The Impact of Interferon Beta-1b Therapy on Thyroid Function and Autoimmunity Among COVID-19 Survivors - Lui, David Tak Wai; Hung, Ivan Fan Ngai; Lee, Chi Ho; Lee, Alan Chun Hong; Tam, Anthony Raymond; Pang, Polly; Ho, Tip Yin; Cheung, Chloe Yu Yan; Fong, Carol Ho Yi; Law, Chun Yiu; To, Kelvin Kai Wang; Lam, Ching Wan; et al. (Frontiers in Endocrinology, 2021)
Background: Interferon beta-1b (IFN) is an effective COVID-19 treatment. We aimed to evaluate the impact of short-term IFN on incident thyroid dysfunction and autoimmunity among COVID-19 survivors. Methods: We included consecutive adults without known thyroid disorder admitted to Queen Mary Hospital for COVID-19 from July 2020 to January 2021 who had thyroid function tests (TFTs) and anti-thyroid antibodies measured both on admission and at three months. Results: 226 patients were included (median age 55.0 years; 49.6% men): 135 were IFN-treated. There tended to be more abnormal TFTs upon reassessment in IFN-treated patients (8.1% vs 2.2%, p=0.080). 179 patients (65.4% IFN-treated) had complete reassessment of anti-thyroid antibodies. There were significant increases in titres of both anti-thyroid peroxidase antibodies (anti-TPO: baseline 29.21 units [IQR: 14.97 – 67.14] vs reassessment 34.30 units [IQR: 18.82 – 94.65], p<0.001) and anti-thyroglobulin antibodies (anti-Tg: baseline 8.23 units [IQR: 5.40 – 18.44] vs reassessment 9.14 units [IQR: 6.83 – 17.17], p=0.001) in the IFN-treated group but not IFN-naïve group. IFN treatment (standardized beta 0.245, p=0.001) was independently associated with changes in anti-TPO titre. Of the 143 patients negative for anti-TPO at baseline, 8 became anti-TPO positive upon reassessment (seven IFN-treated; one IFN-naïve). Incident anti-TPO positivity was more likely to be associated with abnormal TFTs upon reassessment (phi 0.188, p=0.025). Conclusion: IFN for COVID-19 was associated with increases in anti-thyroid antibody titres, and a trend of more incident anti-TPO positivity and abnormal TFTs during convalescence. Our findings suggest clinicians to monitor the thyroid function and anti-thyroid antibodies among IFN-treated COVID-19 survivors.